RIPK1 signaling pathways: implications for autoimmune and neuroinflammatory diseases - Pajulas, Abigail; Sims, Jonathan T.; Hanson, Eric P.; Vendel, Andrew C. (Frontiers in Immunology, 2025)
Receptor-interacting protein kinase 1 (RIPK1), which regulates cell death and survival pathways, is a promising therapeutic target for the treatment of several autoimmune, inflammatory, and neurodegenerative diseases, having important roles in inflammation, apoptosis, and necroptosis. In this review, we describe recent insights that help elucidate the molecular mechanisms of signaling pathways reliant on RIPK1, focusing on its scaffolding function and kinase activity. We emphasize the cell type-specific effects of RIPK1, characterizing its role in necroptosis, immune cell regulation, and tissue-specific responses. Lastly, we present the relevance of RIPK1 in autoimmune and inflammatory diseases, while highlighting the clinical landscape for RIPK1-targeting therapies. All together, this review aims to present recent findings pertaining to RIPK1 signaling and discuss its potential as a therapeutic target in diseases.